Terminological Analysis of Public Administration. Key Research Outcomes - Cibikova, Ingrid (Communications - Scientific letters of the University of Zilina, 2012)
The research carried out by the author has been focused on the terminological analysis of Slovak and English terms used in the subject field of public administration especially in translation. The author based her research on the theoretical knowledge gained in the field of terminology, as the field researched and part of translatology, interdisciplinary science and textual linguistics. The author presented current trends in Francophone terminological thinking and practice: socioterminological, textual and translation terminology. A large number of public administration terms are analyzed thoroughly, compared to concepts, definitions and contextual match. The author also monitors Slovak terminology and describes all the synonyms for the English equivalents. After the terms are discussed with experts, preferred English equivalents used in practice are given to them. Finally, the author describes the innovative terminological analysis and specifies a term acceptability rating.